2020
DOI: 10.21037/tcr.2020.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels in patients with oral cancer, leukoplakia and submucous fibrosis: a cross-sectional study

Abstract: Background This cross-sectional cohort study aimed to assess the associations between the serum uric acid levels and oral leukoplakia (OL), submucous fibrosis (OSMF) and squamous cell carcinoma (OSCC), and to correlate these with the clinical and histopathological features of these lesions. Methods Fifty-two patients with oral potentially malignant disorders (OPMD) (25 OL and 27 OSMF cases) and 33 OSCC patients with complete clinical and histopathological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…It is well-established that chewing areca nut (Areca catechu) is the major causative factor of OSF (IARC, 2004). Areca nut increases cells' oxidative stress that leads to DNA damage (Yadav et al, 2020). The disruption of cyclin-dependent kinases has also been postulated in oral carcinogenesis (Kujan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that chewing areca nut (Areca catechu) is the major causative factor of OSF (IARC, 2004). Areca nut increases cells' oxidative stress that leads to DNA damage (Yadav et al, 2020). The disruption of cyclin-dependent kinases has also been postulated in oral carcinogenesis (Kujan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Yadav et al based on the assessment of serum uric acid in leukoplakia, submucous fibrosis, and squamous cell carcinoma, it was concluded that serum uric acid levels were reduced in patients with oral leukoplakia (OL) and OSCC, but they were increased in patients with oral submucous fibrosis (OSMF) when compared with the healthy control [ 29 ]. Given the linear association between serum and salivary uric acid, further studies might be carried out to associate salivary uric acid levels with premalignant and malignant conditions of the oral cavity.…”
Section: Reviewmentioning
confidence: 99%
“…Hyperuricemia is an important and independent risk factor for cardiovascular disease and cardiovascular risk factors, such as hypertension, hyperlipidemia, type 2 diabetes, obesity, insulin resistance, and metabolic syndrome [ 6 ]. Many studies have shown that the increase of SUA level is an independent risk factor for malignant tumor occurrence and poor prognosis [ 7 , 8 ]. The proinflammatory properties of SUA may play an important role in the occurrence and development of cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%